White Coat Effect: The Making of the Patient-Physician Relationship in Modern Europe - Hanulík, Vladan (Dějiny – teorie – kritika, 2019)
A white coat effect is the term used to describe the situation in which a patient experiences a physical reaction on interaction with a physician in connection with medical treatment. The white coat effect is historically rooted in the process of differentiation in the style of thought regarding patients’ status and their role in the diagnostic and therapeutic process. In the period of bedside medicine, the medical profession commanded little corporate power and therapeutic nihilism led patients to distrust the outcomes of professional treatment. Relationships between medical professionals and patients were marked by patients’ mistrust in the doctor as a professional who understood the secrets of nature. With modern scientific progress in the nineteenth century, the patient’s status changed significantly. The patientʼs personal opinion and reflection of their health condition became irrelevant after the introduction of modern diagnostic tools. The patient’s body no longer even needed to be present for the medical examination: diagnosis could take place using samples of the patient’s tissue, blood, cells or genes and their voice and opinion were not required. Hierarchical and imbalanced interactions between patients and physicians became an integral part of modern medicine. As a result, interaction with medical professionals is accompanied by anxiety, fear, and an inferiority complex, physically embodied in the white coat effect.